Asymmetrically twisted anthracene derivatives as highly efficient deep-blue emitters for organic light-emitting diodes. Issue 38 (9th September 2015) - He, Chuanyou; Guo, Haoqing; Peng, Qiming; Dong, Shengzhi; Li, Feng
Abstract : Two anthracene derivatives with asymmetrically twisted molecular structure achieved high thermal stability and high-efficiency deep-blue emissions. Abstract : Deep-blue emission is particularly important for applications of organic light-emitting diodes (OLEDs) in full colour flat-panel displays and solid-state lighting resources. Two asymmetrically twisted anthracene derivatives, 4, 5-diphenyl-1, 2-bis(4-(10-phenylanthracen-9-yl)phenyl)-1 H -imidazole (DPA-PIM) and 1, 2-bis(4-(10-phenylanthracen-9-yl)phenyl)-1 H -phen-anthro[9, 10- d ]imidazole (DPA-PPI), for deep-blue OLEDs have been designed and synthesized. The asymmetrically twisted conformations between anthracene and imidazole units in compounds efficiently interrupt molecular π-conjugation and inhibit π–π intermolecular interactions, resulting in high thermal stability and efficient deep-blue emission. The two anthracene derivatives in non-doped OLEDs exhibited blue emission. In particular, the non-doped device based on DPA-PIM achieved an external quantum efficiency (EQE) of 6.5% with CIE coordinates of (0.15, 0.08). In addition, the two emitters in doped devices achieved high EQEs of over 5.0% and much purer blue emission with CIE coordinates of (0.15, 0.06) for DPA-PPI and (0.15, 0.05) for DPA-PIM, which nearly match the CIE coordinates of the European Broadcasting Union (EBU) blue standard of (0.15, 0.06).